RELATIONSHIP BETWEEN ECONOMIC STATUS AND STUNTING INCIDENTS IN TODDLERS AGED 12 - 59 MONTHS IN EAST NUSA TENGGARA, INDONESIA - Langotukan, Maria Regina Kewa; Prasetyo, Budi; Irwanto (UNIVERSITAS AIRLANGGA, 2025)
Background: Toddlers who experience stunting generally experience cognitive and motor developmental delays. The incidence of stunting in Balauring village in February 2021 was 39.1%, in August it was 25%. This study aims to determine the stunting rate, analyze the relationship between economic status and parenting patterns on the incidence of stunting in toddlers aged 12-59 months. Method: This type of research is observational analytic using cross-sectional. The sample in this study were parents who had toddlers aged 12 – 59 months who were registered on the register at the Balauring village posyandu, biological parents who cared for the toddlers, lived at home with the toddlers, and were willing to be respondents. The sample size was 60 respondents. Sampling technique. Non Random Sampling atau tidak acak dengan consecutive sampling. The related variable is stunting, while the independent variables are economic status and parenting patterns. Bivariate data analysis used the chi square test. Results: This research showed that there were 18 stunted toddlers with a low economy (54.5%) and 15 stunted toddlers with a low economy (45.5%) in Balauring village. A total of 26 toddlers were stunted (56.5%) toddlers were not stunted with inappropriate parenting patterns in providing food in Balauring village. There was no relationship between economic status and the incidence of stunting in toddlers aged 12 – 59 months in Balauring village with a value of ρ<0.511 ( ρ<0.05). There is no relationship between the parenting style of giving food and the incidence of stunting in toddlers aged 12 – 59 months in Balauring village with p=0.606 (p<0.05). Conclusion: This research shows that there is no relationship between economic status, parenting patterns and the incidence of stunting in toddlers aged 12 - 59 months in Balauring village.